Переосмислення минулого: доля будівель соціалістичного реалізму у столицях країн колишнього східного блоку - Лінда, С. М.; Шулдан, Л. О.; Linda, S.; Shuldan, L. (Видавництво Львівської політехніки, 2018)
Розглянуто проблему трактування будівель доби соціалістичного реалізму у столицях країн колишнього соціалістичного табору. Репрезентовано різне ставлення до цих об’єктів у Бухаресті, Софії, Празі та Варшаві, що зумовлено відмінною інтерпре¬тацією свого соціалістичного минулого

In 1992 an extremely interesting study by professor Umea University of Sweden, Anders Aman, “Architecture and Ideology in Eastern Europe during the Stalin era: an aspect of the history of the Cold War” was published. It was a rare and valuable work, which discussed the expansion of the architecture of socialist realism from Moscow to the west in order to establish a communist ideology. Expansion often took forms rather aggressive and brutal, however, the ideologists of the regime were positioned as good and visualized in the form of the construction of new buildings in the forms of socialist realism. It will soon be 30 years since the socialist camp became a story. The governments of the country have changed, the vectors of their development and geopolitical priorities. But there are buildings. They stand and remind of a complex past, which many recall with nostalgia, and many with pain. These buildings have now become part of a historic heritage, often an “undesirable” heritage, and in many countries a proper attitude towards these buildings has clearly formed, which is likely to reflect the attitude towards the socialist past, and perhaps actual relations with Russia as the successor to the Soviet Union. The purpose of the article is to find out the value of buildings of the era of socialist realism in the modern ideological and cultural space of the capitals of the countries of the former socialist camp on the example of Prague, Bucharest, Sofia, and Warsaw. Thirty years is still an insufficient chronological distance to appreciate the legacy of socialist realism. One statement, it seems, is still undoubted. This architecture is a very serious phenomenon whose significance is not limited to architecture alone. These buildings have their well-established and recognizable architectural vocabulary, they excite genuine emotions, make them think over many issues related to our relationship with the past (and, hence, to the future) and with the constant search for our own identity. Their different fate today is a kind of “historical boomerang” in relation to the history of their uprising. The more aggressive and brutal forms were their construction, the more rejection can be observed in modern society. Examples of this are the attitude towards highs in Prague and Warsaw. In the first case, the initiative came from the pro-Soviet Czechoslovak government, Czechoslovak architects designed the then-friendly Druzhba hotel, the building itself never played a significant role in the architectural image of the city and was located far from the historic center. Today, the hotel is relatively calm, there is no talk of dismantling, and even the star - a symbol of communist rule - remained in place. Otherwise the situation in Warsaw: The Palace of Culture was designed and built by Soviet architects in record time, set in the heart of the city, built at a time when Warsaw was in ruins in need of money for housing and infrastructure renovation. However, the Soviet Union “presented” a gigantic palace that nobody asked for. He needed only as a symbol of ideological domination, and this is what he interpreted today (although, ironically, the palace became the symbol of today's Warsaw). The dismantling of stars and other communist symbols did not change anything: the talk of his disassembly constantly causes heated discussions. Instead, in Sofia and Bucharest, de-communization was limited to eliminating stars from coats of arms on the facades of buildings. The buildings stand, perform their functions, and it seems the story of their uprising is just a story page. Perhaps this is also supported by a rather stable political relationship with today's Russia, as the successor to the Soviet Union. The history of the fate of the Stalinist skyscrapers in the capitals of the countries of the socialist camp is still being written. Still the attitude towards them is formed, which reflects the relation to its past, and the future of some buildings and still unpredictable
Rethinking of the past: the fate of socialist realism buildings in the capitals of former eastern block countries
Keywords: архітектура; соціалістичний реалізм; столиці країн колишнього соціалістичного табору; architecture; socialist realism; capitals of the countries of the former socialist camp; 72.01(03)